Internalization of External Tau Aggregates Co-Localize with Early Endocytic Markers and Lysosomes - Melo-Hurtado, F; Caballero-Alvial, L (Elsevier B.V., 2025)
Tau s spread and internalization are related to disease progression in Alzheimer s disease and tauopathies. Tau internalization plays a critical role in the spreading. The cells involved in brain surveillance involved in the clearance of aggregates include parenchymal-border macrophages (microglia), perivascular macrophages, and meningeal and choroid plexus macrophages. However, in events such as strokes, or tau amyloids can breach the blood-brain barrier (BBB). Facilitating the dissemination of aggregates. Thus, we evaluated whether the tau aggregates have effect over a semi-permeable layer such as DOPC. Nano-indentation showed that tau monomers of full length and tau 4R (microtubule binding domain) interact differently with DOPC, and the amyloids increase the Fp (critical force) but not disrupt the DOPC. Then, to analyze the effect of aggregates on N2a cells, we incubated tau aggregates for 24 h; resulting in the decrease of axon-like structures compromising the cell integrity. Afterwards, cultured tau aggregates with raw 264.7 cells (mouse macrophages) showed that the 4R microtubule-binding domain co-localize with Rab5 and Lamp1, suggesting a key role to lysosomes in the clearance of tau aggregates. © 2024